The European Iceberg : Creativity in Germany and Italy Today - Celant, Germano (Toronto : Art Gallery of Ontario, 1985)
Aulenti, Gae ; Böhm, Gottfried ; Gregotti, Vittorio ; Hollein, Hans ; Kleihues, Josef Paul ; Piano, Renzo ; Rossi, Aldo ; Valle, Gino ; Anselmo, Giovanni ; Bagnoli, Marco ; Baselitz, Georg ; Baumgarten, Lothar ; Beuys, Joseph ; Burri, Alberto ; Calzolari, Pier Paulo ; Cucchi, Enzo ; Darboven, Hanne ; De Maria, Nicola ; Fabro, Luciano, Gerdes, Ludger ; Horn, Rebecca ; Immendorff, Jörg ; Kiefer, Anselm ; Kounellis, Jannis ; Lüpertz, Markus ; Merz, Gerhard ; Merz, Mario ; Mucha, Reinhard ; Paladino, Mimmo ; Paolini, Giulio ; Penck, A.R. ; Penone, Giuseppe ; Pistoletto, Michelangelo ; Polke, Sigmar ; Richter, Gerhard ; Salomé ; etc.
Based on an exhibition held at the Art Gallery of Ontario, Toronto , February 8-April 7, 1985
English
kunstcatalogus
Keywords: Duitsland; Italië